Myeloid-Derived Suppressor Cells in Trypanosoma cruzi Infection - Fresno, Manuel; Gironès, Núria (Frontiers in Cellular and Infection Microbiology, 2021)
Myeloid-derived suppressor cells (MDSCs) are immature heterogeneous myeloid cells that expand in pathologic conditions as cancer, trauma, and infection. Although characterization of MDSCs is continuously revisited, the best feature is their suppressor activity. There are many markers for MDSC identification, it is distinctive that they express inducible nitric oxide synthase (iNOS) and arginase 1, which can mediate immune suppression. MDSCs can have a medullary origin as a result of emergency myelopoiesis, but also can have an extramedullary origin. Early studies on Trypanosoma cruzi infection showed severe immunosuppression, and several mechanisms involving parasite antigens and host cell mediators were described as inhibition of IL-2 and IL-2R. Another mechanism of immunosuppression involving tumor necrosis factor/interferon γ-dependent nitric oxide production by inducible nitric oxide synthase was also described. Moreover, other studies showed that nitric oxide was produced by CD11b+ Gr-1+ MDSCs in the spleen, and later iNOS and arginase 1 expressed in CD11b+Ly6C+Ly6Glo monocytic MDSC were found in spleen and heart of T. cruzi infected mice that suppressed T cell proliferation. Uncontrolled expansion of monocytic MDSCs leads to L-arginine depletion which hinders nitric oxide production leading to death. Supplement of L-arginine partially reverts L-arginine depletion and survival, suggesting that L-arginine could be administered along with anti-parasitical drugs. On the other hand, pharmacological inhibition of MDSCs leads to death in mice, suggesting that some expansion of MDSCs is needed for an efficient immune response. The role of signaling molecules mediating immune suppression as reactive oxygen species, reactive nitrogen species, as well as prostaglandin E2, characteristics of MDSCs, in T. cruzi infection is not fully understood. We review and discuss the role of these reactive species mediators produced by MDSCs. Finally, we discuss the latest results that link the SLAMF1 immune receptor with reactive oxygen species. Interaction of the parasite with the SLAMF1 modulates parasite virulence through myeloid cell infectivity and reactive oxygen species production. We discuss the possible strategies for targeting MDSCs and SLAMF1 receptor in acute Trypanosoma cruzi infection in mice, to evaluate a possible translational application in human acute infections.